Bibliometric Review of Islamic Economics Covering Growth Patterns for the Period 2000–2024 - Judijanto, Loso (West Science Islamic Studies, 2026)
This study provides a comprehensive bibliometric review of Islamic economics research published between 2000 and 2024, with the aim of mapping growth patterns, thematic evolution, intellectual structure, and collaboration networks within the field. Using bibliometric techniques and network visualization tools, the study analyzes publication trends, keyword co-occurrence, citation structures, and author, institutional, and country-level collaborations based on data retrieved from the Scopus database. The findings reveal a significant expansion of scholarly output over the past two decades, accompanied by a clear shift from normative and doctrinal discussions toward applied, empirical, and interdisciplinary research. Core themes have evolved from religion, Islamic law, and historical perspectives to finance-led and development-oriented topics such as Islamic finance, waqf, fintech, poverty alleviation, sustainability, and economic growth. Network analyses indicate that while Islamic economics research is increasingly internationalized, collaboration remains concentrated among a limited number of authors, institutions, and countries, with Malaysia, the United Kingdom, the United States, and Australia serving as key bridging hubs. Overall, the study highlights the intellectual maturation of Islamic economics as a field and underscores its growing relevance in addressing contemporary challenges related to inclusive growth, ethical finance, and sustainable development.